A posteriori error estimation and adaptivity for elliptic optimal control problems with state constraints - Benedix, Olaf; Vexler, Boris (Computational optimization and applications, 2009)
In this paper optimal control problems governed by elliptic semilinear equations and subject to pointwise state constraints are considered. These problems are discretized using finite element methods and a posteriori error estimates are derived assessing the error with respect to the cost functional. These estimates are used to obtain quantitative information on the discretization error as well as for guiding an adaptive algorithm for local mesh refinement. Numerical examples illustrate the behavior of the method.